USE OF PLANT BIOTECHNOLOGY IN CROP IMPROVEMENT AND GENETIC ENGINEERING (International Journal of Food and Nutritional Sciences, 2022)
The power of genetic engineering has made it possible to modify the genetic makeup of agricultural plants. Transgenic technology, often known as recombinant DNA technology, is responsible for this. Plants in a crop may have a lot of desirable traits, but the presence of even a few undesirable traits might cause the crop's area and output to be severely constrained. Because of this, many farmers have been forced to switch to growing other types of food. Issues brought on by biotic and abiotic stressors may also be addressed with the use of recombinant technologies. There is always a chance to take stock of human endeavor in a given field and plot a course for the future because to the fluid nature of time. Researchers are required to respond to the dynamic global situation in which they work since science and technology cannot exist in a vacuum. Conclusion New plant features and varieties developed using plant biotechnology need to be mass-produced to be economically viable and to meet the needs of both commercial producers and the general public.